Pruebas a equipos seccionadores en subestaciones eléctricas (2021)
The purpose of the degree work is to design the protocols that are applied in a substation to carry out the necessary tests to disconnectors, which can be carried out at start-up or to verify the current operating status. The protocols establish the procedures and analysis on how the necessary tests should be carried out on disconnectors in electrical substations, in accordance with the International and National standards and recommendations given by the manufacturer.